Force sensing with 1 mm fiber Bragg gratings for flexible endoscopic surgical robots - Lai, Wenjie (2020)
This article presents a novel force sensor to detect the distal force of tendon-sheath mechanisms (TSMs) in flexible endoscopic surgical robots. We propose to measure the compression force on the sheath at the distal end so that the tension force on the tendon, which equals the compression force on the sheath, can be obtained. With this approach, a new force sensor made up of a 1 mm fiber Bragg grating attached to a 3 mm long nitinol tube was developed to measure the compression force exerted on the sheath. Mechanics analysis and verification tests were conducted to characterize the relationship between tension and compression on a TSM. Force calibrations, hysteresis study, and temperature compensation verification tests on the sensor were carried out. The force sensor has a measurement error of 0.178 N and a sensitivity of 34.14 pm/N. Applications of the sensor in a TSM-driven robotic grasper and a tendon-driven continuum robot were demonstrated. This force sensor has salient advantages: it is small, structurally simple, electrically passive, temperature-compensated, easy to assemble and disassemble, flexible, and biocompatible. This proposed approach with the new force sensor can also be applied to both TSM-driven systems and tendon-driven systems such as robotic fingers/hands, wearable devices, surgical catheters, and rehabilitation devices.